Chronic NOD2 stimulation by MDP confers protection against parthanatos through M2b macrophage polarization in RAW264.7 cells - Mansilla, Florencia Celeste; Miraglia, Maria Cruz; Maidana, Silvina Soledad; Randazzo, Cecilia Paola; Capozzo, Alejandra (Elsevier, 2024)
Innate immune cells show enhanced responsiveness to secondary challenges after an initial non-related stimulation (Trained Innate Immunity, TII). Acute NOD2 activation by Muramyl-Dipeptide (MDP) promotes TII inducing the secretion of pro-inflammatory mediators, while a sustained MDP-stimulation down-regulates the inflammatory response, restoring tolerance. Here we characterized in-vitro the response of murine macrophages to lipopolysaccharide (LPS) challenge under NOD2-chronic stimulation. RAW264.7 cells were trained with MDP (1 μg/ml, 48 h) and challenged with LPS (5 μg/ml, 24 h). Trained cells formed multinucleated giant cells with increased phagocytosis rates compared to untrained/challenged cells. They showed a reduced mitochondrial activity and a switch to aerobic glycolysis. TNF-α, ROS and NO were upregulated in both trained and untrained cultures (MDP+, MDP- cells, p > 0.05); while IL-10, IL-6 IL-12 and MHCII were upregulated only in trained cells after LPS challenge (MDP + LPS+, p < 0.05). A slight upregulation in the expression of B7.2 was also observed in this group, although differences were not statistically significant. MDP-training induced resistance to LPS challenge (p < 0.01). The relative expression of PARP-1 was downregulated after the LPS challenge, which may contribute to the regulatory milieu and to the innate memory mechanisms exhibited by MDP-trained cells. Our results demonstrate that a sustained MDP-training polarizes murine macrophages towards a M2b profile, inhibiting parthanatos. These results may impact on the development of strategies to immunomodulate processes in which inflammation should be controlled.